The impact of co-production on frontline accountability: the case of the conciliation service - Tuurnas, Sanna; Rannisto, Pasi-Heikki; Stenvall, Jari (2016)
Mixing of roles between professionals, volunteers and service users creates a new, complex environment in which to produce and deliver public services. In this kind of environment, the issues of accountability become ever more important. This article presents a qualitative case study of co-production between volunteers and professionals in the legally regulated restorative justice services in Finland. Theoretically, we draw together the concept of citizen co-production with the literature on street-level bureaucracy and accountability. As a result of the study, we can say that co-production between volunteers and professionals increases accountability ties. In particular, the meaning of process-centred accountability is salient in horizontal accountability relations. Thus, co-production as a governance arrangement changes the working culture of public service professionals. In the new partnerships, although not entirely horizontal, we can recognize a seed for cultural change for professionalized public service organizations.
Keywords: Public administration